2020
DOI: 10.3390/toxins12060376
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Enzyme and Non-Label Sensitive Fluorescent Aptasensor Based on Simulation-Assisted and Target-Triggered Hairpin Probe Self-Assembly for Ochratoxin a Detection

Abstract: The monitoring and control of mycotoxins has caused widespread concern due to their adverse effects on human health. In this research, a simple, sensitive and non-label fluorescent aptasensor has been reported for mycotoxin ochratoxin A (OTA) detection based on high selectivity of aptamers and amplification of non-enzyme hybridization chain reaction (HCR). After the introduction of OTA, the aptamer portion of hairpin probe H1 will combine with OTA to form OTA-aptamer complexes. Subsequently, the remainder of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In addition to immunoanalytical (antibody-based) setups, the development of a label-free aptamer-based fluorescent sensor is reported by Qian et al [ 18 ] for the detection of OTA. The aptasensor utilizing a nucleotide recombination hybridization chain reaction amplification element allows high selectivity for OTA with a LOD of 2.0 pg/mL (4.9 pM).…”
Section: Methods Developmentmentioning
confidence: 99%
“…In addition to immunoanalytical (antibody-based) setups, the development of a label-free aptamer-based fluorescent sensor is reported by Qian et al [ 18 ] for the detection of OTA. The aptasensor utilizing a nucleotide recombination hybridization chain reaction amplification element allows high selectivity for OTA with a LOD of 2.0 pg/mL (4.9 pM).…”
Section: Methods Developmentmentioning
confidence: 99%
“…In a recent study, an OTA detection method based on the amplification of non-enzyme hybridization chain reaction was described (Qian et al, 2020 ). In the presence of OTA, the fluorescent signals are significantly enhanced due to the interaction of G4 with N-methylmesoporphyrin IX.…”
Section: G-quadruplex-based Detection Methods For Otamentioning
confidence: 99%
“…Fluorescent aptasensors based on DNA amplification techniques, such as nuclease-aided recycling amplification, , HCR, and RCA were also applied for the sensitive detection of OTA. For example, in a structure-switching aptamer approach, RNase H was applied to cleave the RNA in cDNA/RNA hybrid and release the cDNA, leading to cDNA recycling signal amplification .…”
Section: Application Of Fluorescent Aptasensor For the Detection Of F...mentioning
confidence: 99%
“…In structure-switching aptasensors that utilized the adsorption affinity of dye-labeled ssDNA with GO, cDNA hybridized with a specifically designed hairpin DNA and Exo III was applied to digest dsDNA for cDNA release to generate a cyclic hybridization–hydrolysis process for signal amplification . Qian et al reported a simple, sensitive, and label-free fluorescent aptasensor for OTA detection through NMM binding with G4 structures generated in HCR products . The study combined computer simulation and biological experiments.…”
Section: Application Of Fluorescent Aptasensor For the Detection Of F...mentioning
confidence: 99%